Vulnerability to stroke: implications of perinatal programming of the hypothalamic-pituitary-adrenal axis - Craft, Tara K.; DeVries, Courtney (Frontiers in Behavioral Neuroscience, 2009)
Chronic stress is capable of exacerbating each major, modifiable, endogenous risk factor for cerebrovascular and cardiovascular disease. Indeed, exposure to stress can increase both the incidence and severity of stroke, presumably through activation of the hypothalamic-pituitary-adrenal (HPA) axis. Now that characterization of the mechanisms underlying epigenetic programming of the HPA axis is well underway, there has been renewed interest in examining the role of early environment on the evolution of health conditions across the entire lifespan. Indeed, neonatal manipulations in rodents that reduce stress-responsivity, and subsequent life-time exposure to glucocorticoids, are associated with a reduction in the development of neuroendocrine, neuroanatomical, and cognitive dysfunctions that typically progress with age. Although improved day to day regulation of the HPA axis also may be accompanied by a decrease in stroke risk, evidence from rodent studies suggest that an associated cost could be increased susceptibility to inflammation and neuronal death in the event that a stroke does occur and the individual is exposed to persistently elevated corticosteroids. Given its importance in regulation of health and disease states, any long-term modulation of the HPA axis is likely to be associated with both benefits and potential risks. The goals of this review article are to examine 1) the clinical and experimental data suggesting that neonatal experiences can shape HPA axis regulation, 2) the influence of stress and the HPA axis on stroke incidence and severity, and 3) the potential for neonatal programming of the HPA axis to impact adult cerebrovascular health.